Demography and Polygyny in a Southern Sudanese Agro-pastoralist Society - Roth, Eric Abella; Kurup, K. B. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1988)
Survey data from eight Toposa villages were used to examine the demographic effects of polygyny upon this Southern Sudanese agro-pastoralist population. Direct age standardization of fertility rates revealed lower fertility for women in polygynous unions, as measured by maternal age and marital duration. Indirect techniques of mortality estimation indicated higher childhood mortality for offspring of polygynous marriages. The underlying rationale for these demographic differentials is attributed to Toposa social structure, including the economic value of women, gerontocracy and residential patterns.